2015
DOI: 10.18632/oncotarget.3441
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of EGFR and c-ABL suppresses the growth of triple-negative breast cancer growth through inhibition of HOTAIR

Abstract: Triple-negative breast cancer (TNBC) does not express conventional therapeutic targets and is the only type of malignant breast cancer for which no designated FDA-approved targeted therapy is available. Although overexpression of epidermal growth factor receptor (EGFR) is frequently found in TNBC, the therapeutic effect of EGFR inhibitors in TNBC has been underwhelming. Here we show that co-treatment with clinically validated inhibitors of c-ABL (imatinib) and EGFR (lapatinib) results in synergistic growth inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 43 publications
(43 reference statements)
3
62
1
Order By: Relevance
“…HOTAIR has been extensively studied in cancer [22]. Its expression has been shown to regulate breast and lung cancer cell growth and metastasis [23, 24]. In our study, up-regulation of XLOC_008466 was confirmed in NSCLC tissues and is associated with lymph node metastasis and the TNM stage.…”
Section: Discussionsupporting
confidence: 63%
“…HOTAIR has been extensively studied in cancer [22]. Its expression has been shown to regulate breast and lung cancer cell growth and metastasis [23, 24]. In our study, up-regulation of XLOC_008466 was confirmed in NSCLC tissues and is associated with lymph node metastasis and the TNM stage.…”
Section: Discussionsupporting
confidence: 63%
“…In estrogen receptor (ER)-positive breast cancer cells, ABL is a functional partner of ERs, and inhibition of ABL resulted in sensitization to anti-estrogen therapies with tamoxifen, fulvestrant and aromatase inhibitors (Esparza-Lopez et al, 2013;Weigel et al, 2013;Zhao et al, 2011Zhao et al, , 2010. In addition, inhibition of ABL1 has been reported to sensitize breast cancer cells to the EGFR and ERBB receptor tyrosine kinase inhibitor lapatinib Stuhlmiller et al, 2015;Wang et al, 2015), and prostate and renal cancer cells to inhibitors of heat shock protein 90 (Hsp90) (Dunn et al, 2015) (see poster).…”
Section: Role For Abl Kinases In Solid Tumorsmentioning
confidence: 99%
“…This facilitates the ligand-independent activation of ER, which contributes to tamoxifen resistance [179]. Moreover, upregulation of HOTAIR was also found in triple-negative breast cancer (TNBC) cell lines in addition to primary breast tumors [180]. Suppression of HOTAIR expression by co-treatment with clinically validated inhibitors of c-ABL (imatinib) and EGFR (lapatinib) resulted in synergistic growth inhibition in TNBC cells [180].…”
Section: Epigenetic Regulatorsmentioning
confidence: 99%
“…Moreover, upregulation of HOTAIR was also found in triple-negative breast cancer (TNBC) cell lines in addition to primary breast tumors [180]. Suppression of HOTAIR expression by co-treatment with clinically validated inhibitors of c-ABL (imatinib) and EGFR (lapatinib) resulted in synergistic growth inhibition in TNBC cells [180]. This dual treatment effect was mediated by blocking nuclear expression of b-catenin and preventing its recruitment to the HOTAIR promoter [180].…”
Section: Epigenetic Regulatorsmentioning
confidence: 99%
See 1 more Smart Citation